Intraoperative use of cone-beam computed tomography in a cadaveric ossified cochlea model - Barker, Emma (2009)
OBJECTIVES: To describes a cadaveric temporal bone model of labyrinthitis ossificans and investigate the utility of intra-operative C-arm computed tomography (CBCT) in facilitating cochlear implantation. DESIGN: Cadaveric temporal bone study. METHODS: Five cadaveric heads had cement introduced into the 10 cochleas. CBCT and a conventional CT scans were compared to asses the extent of cochlear obliteration. The cement was drilled-out (under CBCT guidance, if required) and a cochlear implant electrode arrays (from 3 different manufacturers) inserted. RESULTS: CBCT images demonstrated temporal bone anatomy and the extent of cochlear obliteration as clearly as conventional CT in all cases. Intra-operative CBCT guided drilling and facilitated electrode placement in 2 out of 5 heads (3/10 ears). Streak-artifact from the electrodes of two devices partially obscured image clarity. CONCLUSIONS: The obliterated cochlear model reproduced a disease-ossified cochlear both radiographically and surgically. CBCT is useful for intra-operative imaging, to facilitate electrode array placement in the obliterated or congenitally abnormal cochlea.